Effects of length of ensiling and maturity group on chemical composition and in vitro ruminal degradability of whole‐crop maize. (17th April 2018) - Gerlach, K.; Pfau, F.; Pries, M.; Hünting, K.; Weiß, K.; Richardt, W.; Südekum, K.‐H.
Abstract: Nine hybrids (three maturity groups, dry matter 343 ± 5.6 g/kg) of whole‐crop maize were ensiled in eight replicates in laboratory‐scale silos. Each hybrid was sampled at harvest and after 30, 60, 90 and 120 days (d) of ensiling. Samples were analysed for chemical composition (proximate constituents, fermentation products and pH), starch, non‐protein N (NPN) and NH3 ‐N. Each sample and its neutral detergent fibre (NDF) fraction were incubated in the Hohenheim gas test system. In vitro gas production was measured after 0, 2, 4, 8, 12, 16, 24, 36, 48, 72 and 96 hr of incubation. Gas production of the neutral detergent soluble (NDS) fraction (mainly starch) was calculated using a curve subtraction method. Gas production dynamics over time were estimated using a nonlinear regression equation; afterwards, a two‐factorial analysis of variance (storage length, maturity group and their interaction) using the general linear models procedure was conducted. After 30 d, all silages were well fermented. Most fermentation products and proximate constituents only changed until 30 or maximum 60 d of ensiling. Only few changes in in vitro nutrient degradability were detected after the first 30 d or as influenced by maturity group. Ensiling per se increased the ruminal degradability of the NDS, but there was no further increase caused by a prolonged duration of storage. However, extensive changes in crude protein fractions occurred with a linear increase in NPN and NH3 ‐N compounds from 0 to 120 d of storage, indicating continual protein and amino acid degradation.